(3NdGUI GdhaG HCNHGQ OGQ GdeUWais - (3Ydj Hf YHO Gddg GdMSjfj GdSeghOj GdTGaYjs
(3ChdgG (B:s
(3GdMeO ddg GdPi TQa WGHI hHYO abO TaYJ HGNHGQ GdMHjHI GdeMHI hCdaJ ai Pdc cJGHkG MGadkG SejJg GdhaG HCNHGQ OGQ GdeUWai Udi Gddg Ydjg hSde s
(3BNQgG (B:s
(3bGd GdgLQi heQHjf WQjb Ci JSdc gfGc Edi Hjf hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg hSde s
(3GdfSNI eMdGI heLOhdI HGdPgHs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI YGQa MceJ HGdeOjfI GdefhQI(B((3JGQjN (B99) s
Keywords: (3GdJGQjNs